Research and Comparisons Regarding the Evolution of Cattle Population in Romania and Some Member States of the European Union - Ramona Ciolac; Ioan Csosz; Diana Marin; Simona Marin; Ana Maria Dincu; Calina Marinau; Ioana Balan (Scientific Papers Animal Science and Biotechnologies, 2023)
Cattle husbadry occupy and will occupy a priority place in the economy of animal production in our country. Their increasing importance is given by the variety of products that they provide. Cattle husbadry is a traditional activity of the country. Variety of products they carry out, reduced energy consumption and nature kind of feed they consume, gives growth and  and exploitation of cattle activities a sustainable and perpective character. There is also the possibility to export beef cattle witch can provide large profits for producers. Can be regarded as a source for trade and also provide stability of employment in rural and mountain area.